The letter and the spirit of nineteenth-century American literature : justice, politics, and theology - Loebel, Thomas, 1965- (McGill-Queen's University Press, 2005)
"Moving back to the trial of Anne Hutchinson in Puritan Massachusetts and the captivity narrative of Mary Rowlandson in order to analyse theo-political signification, The Letter and the Spirit of Nineteenth-Century American Literature provides a new context for examining the politically performative function of language in such texts as The Scarlet Letter, Uncle Tom's Cabin, and Waiting for the Verdict."--Jacket